Phytochemistry and Evidence-Based Traditional Uses of the Genus Achillea L.: An Update (2011-2021) - Christina Barda; Maria-Eleni Grafakou; Ekaterina-Michaela Tomou; Helen Skaltsa (MDPI AG, 2021)
Knowledge within the field of phytochemistry research has accelerated at a tremendous speed. The excess of literature reports featuring plants of high ethnopharmacological importance, in combination with our interest in the Asteraceae family and traditional medicine, led us to acknowledge the value of the Achillea L. genus. In a broad context, the various Achillea species are used around the globe for the prevention and treatment of different diseases, including gastrointestinal problems, haemorrhages, pneumonia, rheumatic pains, diuresis, inflammation, infections, and wounds, as well as menstrual and gynaecologic abnormalities. The present review aims to provide and summarize the recent literature (2011-2021) on the phytochemistry of the Achillea genus. In parallel, this study attempts to bridge the reports on the traditional uses with modern pharmacological data. Research articles that focused on secondary metabolites, traditional uses and pharmacological activities were collected from various scientific databases such as Pubmed, ScienceDirect, Reaxys and Google Scholar. This study revealed the presence of 141 phytochemicals, while 24 traditionally used Achillea spp. were discussed in comparison to current data with an experimental basis.